Scratching of silicon surfaces. (1st May 2019) - Budnitzki, M.; Kuna, M.
Abstract: Nanoscale scratching of silicon surfaces is the elementary abrasive event for various machining techniques including fixed abrasive wire saw slicing, grinding, elliptical ultrasonic cutting and single-point diamond turning. The understanding of this process is essential for improving the surface quality and reducing sub-surface damage. Nanoscratching experiments are performed using a well characterized diamond tip geometry. The finite element method is employed in order to simulate the scratching process with a continuum constitutive model developed for phase transformation in silicon (Budnitzki, M., Kuna, M., 2016. Stress induced phase transitions in silicon. JMPS 95, 64–91). The required material parameters were determined from indentation experiments in a (111) single crystal Si wafer. The simulation results agree very well with data from scratch experiments without requiring additional calibration.